(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study aims to enhance employability through vocational and technical skill development among Nigerian youth and adults. The objectives were to identify the vocational and technical skills needs of Nigerian youth and adults, assess the effectiveness of existing programmes, and investigate the barriers to accessing vocational and technical training in Nigeria. Design/Methodology/Approach: This study used a descriptive cross-sectional survey. To gather information on their vocational and technical skill needs and experiences, 100 Nigerian youths and adults were surveyed. Ten experts in the field of vocational and technical education in Nigeria conducted focus group discussions to elicit more information on the challenges and opportunities faced by the sector. Research Limitation: It relies on self-reported data regarding training efficacy and skill, with limited exploration of the broader contextual factors influencing educational accessibility. Outcomes may not be generalised. Findings: The results of the respondents’ perceptions of the essentiality of vocational and technical skills in their employment showed that skills such as plumbing (3.97), tilling (4.15, automotive repair (4.29), etc., were efficient, with mean scores above 3.05. Communication and technology (ICT) and network marketing (2.27) were found to be less effective. The respondents identified a lack of job opportunities as the biggest challenge facing youth and adults in Nigeria and believed that the government should prioritise vocational and technical education. The study revealed that some of the programmes were often not aligned with the needs of the labour market. Practical Implication: The government should prioritise vocational and technical education, especially in the ICT and Agro sectors. Social Implication: Vocational and technical education can improve employability, increase productivity and reduce poverty. Originality/Value: This study provides insights for improving employability among youth and adults by designing and delivering vocational and technical training programmes that meet labour market needs.